Formação do pensamento de Henri Lefebvre no período entreguerras: aproximações, distanciamentos e apropriações do pensamento marxiano - Marcos Gustavo Pires de Melo (2023)
Henri Lefebvre is a recurrent reference within the so-called urban studies and his concepts inspire different political agendas linked to the right to the city. Nevertheless, the formation of Lefebvre's thought is a subject little explored by researchers who study his theoretical formulations, which ends up generating a paradoxical situation by making him an illustrious unknown. This issue is particularly important when we consider the Marxist dimension of Lefebvre's thought, since understanding the appropriation, interpretation and deployment that the meta philosopher makes of Marx has direct repercussions on the interpretation of Lefebvre's work. The main objective of this work is to explore the formation of Lefebvre's thought in the interwar period of the 20th century from an Intellectual History perspective, which emphasizes the development of thought in relation to the intellectual, social and political context, as a privileged way of understanding its trajectory. At first, the thesis analyzes Lefebvre's philosophical development during the 1920s, demonstrating how he reacted to the main social and political dilemmas of his time through a collective endeavor for the renewal of philosophy known as Philosophies. Next, we explore the transition and the first insertion of Lefebvre in Marxism, based on the project of translation and dissemination of unknown writings published in the Revue Marxiste that feed a particular interpretation of Marxian work by placing dialectical materialism as the central core of Marx's thought. Finally, we try to demonstrate how Lefebvre, throughout the 1930s, deepens and intensifies the effort to disseminate Marx's thought, but is also able to articulate a properly Lefebvrian Marxist approach to the phenomena of mystified consciousness and the rise of fascism. Thus, the thesis contributes to understanding the specificities of Lefebvre's Marxism and the power of his alternative appropriation of Marx in relation to the orthodoxy of his time, as well as demonstrating the importance of the author for the dissemination of Marx's thought in France.